Perspektif Guru Mata Pelajaran Terhadap Profile Profesi Guru BK Dikaitkan Dengan Kaidah Etik BK - Rachmawati Rachmawati; Nadia Aulia Nadhirah; Nandang Budiman (Concept: Journal of Social Humanities and Education, 2023)
This research is aimed at obtaining empirical data regarding the subject teacher's perspective on the guidance and counseling teacher's professional profile in relation to the guidance of counseling ethics. The data collection was carried out by reviewing the literature using the Systematic Literature Review (SLR) through the PRISMA rules systematically. The conclusions of this study indicate that the perspective of subject teachers (subjects) regarding the profile of the counseling teacher profession from the affective and cognitive aspects has a positive response of 70%, and the conative aspect has a positive response of 66%. Judging from the BK ethical principles, the BK teacher has complied with several of them: respecting students' decisions, notifying the boundaries of the relationship between himself and students, not discriminatory, not imposing values, not divulging students' secrets, and not establishing a double relationship. However, this does not rule out the fact that there are still many guidance and counseling teachers in the field who violate the guidance and counseling code of ethics, such as not having a professional license recognized by ABKIN, not having a graduate of the Counselor Professional Education or guidance and counseling bachelor degree, and not having the insight and compatible skills in the field of guidance and counseling.